2016
DOI: 10.1155/2016/7893143
|View full text |Cite
|
Sign up to set email alerts
|

Economic Valuation of Nontimber Forest Products under the Changing Climate in Kilombero District, Tanzania

Abstract: Sustainable collection of Nontimber Forest Products (NTFPs) for trade is an appropriate measure to increase people's adaptive capacity against adverse effects of climate change. However, information on the economic value for NTFPs for subsistence use and trade under the changing climate is inadequate, particularly in households around Iyondo Forest Reserve (IFR), in Kilombero District, Tanzania. The study identified and quantified NTFPs used for subsistence and trade, estimated its economic value, and examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Moreover, the contribution of fuel-woods to mean annual environmental income is associated with a high demand for fuel-wood as main source of cooking energy in the area. This finding is consistent with other studies conducted in Tanzania (Balama et al, 2016;Lusambo, 2016;Kilonzo et al, 2018) and in Uganda (Tugume et al, 2015) and in Zambia (Mulenga, Richardson, Mapemba, & Tembo, 2011). These studies reported that charcoal is the main sources of cooking energy in both urban and rural areas due to lack of affordable sources of energy.…”
Section: Environmental Income Reliance By Distance From Pa Boundarysupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the contribution of fuel-woods to mean annual environmental income is associated with a high demand for fuel-wood as main source of cooking energy in the area. This finding is consistent with other studies conducted in Tanzania (Balama et al, 2016;Lusambo, 2016;Kilonzo et al, 2018) and in Uganda (Tugume et al, 2015) and in Zambia (Mulenga, Richardson, Mapemba, & Tembo, 2011). These studies reported that charcoal is the main sources of cooking energy in both urban and rural areas due to lack of affordable sources of energy.…”
Section: Environmental Income Reliance By Distance From Pa Boundarysupporting
confidence: 92%
“…Another explanation could involve the easier access and availability of environmental resources such as charcoal, firewood, thatch grasses, poles and bush-meat harvested in village lands and illegally within PAs. According to Balama, Augustino, Mwaiteleke, Lusambo, and Makonda (2016) and also Kilonzo, Ndossi, Mauki, and Ochanga (2018), households closest to PAs in Tanzania, are generally more dependent on environmental products despite the restrictions imposed. Another plausible reason for high dependence on environmental cash-income is the higher availability of substitute goods in markets in larger towns that tends to be located further away from PAs.…”
Section: Environmental Income Reliance By Distance From Pa Boundarymentioning
confidence: 99%
“…Several studies have been conducted to assess the potential of NTFPs to alleviate poverty (Ahenkan & Boon, 2010;Cosyns et al, 2011;Meinhold & Darr, 2019) in Ghana and other part of the world. The assessment of local perceptions and the various influencing social factors about climate change, the value addition of NTFPs, and the diverse uses of NTFPs have been insufficiently addressed (Balama et al, 2016;Msalilwa et al, 2013). The study aims to assess the factors that influence the perception of locals on climate change, value addition and multiple use of NTFPs in local communities in Ghana.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…Again, other studies have also assessed the impact of climate change, value addition, and multiple uses of NTFPs and their potential to improve local livelihoods. However, the assessment of local perceptions and the various influencing social factors (education, gender, religion, and age) about climate change, the value addition of NTFPs, and the diverse uses of NTFPs have been insufficiently addressed [26,73]. The study aims to assess the factors that influence the perception of locals on climate change, value addition, and multiple uses of NTFPs in local communities in Ghana.…”
Section: Introductionmentioning
confidence: 99%